2017
DOI: 10.3339/jkspn.2017.21.2.128
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Significance of Extended-spectrum β-lactamase-producing Bacteria in First Pediatric Febrile Urinary Tract Infections and Differences between Age Groups

Abstract: Extended-spectrum β-lactamase-producing bacteria-induced urinary tract infections are increasing and require more potent antibiotics such as carbapenems. We evaluated the clinical significance of extended-spectrum β-lactamase urinary tract infection in children younger than 5 years to select proper antibiotics and determine prognostic factors. Differences were compared between age groups. Methods: We retrospectively studied 288 patients with their first febrile urinary tract infection when they were younger th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 24 publications
1
9
2
Order By: Relevance
“…Our study showed a clear correlation between WBC, BUN, creatinine levels and ESBL-producing organisms. However, Park et al showed no significant association [ 43 ], which indicates the need for further studies to clarify this point and to potentially set guidelines for future management.…”
Section: Discussionmentioning
confidence: 99%
“…Our study showed a clear correlation between WBC, BUN, creatinine levels and ESBL-producing organisms. However, Park et al showed no significant association [ 43 ], which indicates the need for further studies to clarify this point and to potentially set guidelines for future management.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, the study by Park SY and Kim JH revealed that the mean age of infants in the ESBL group (4.31 months old) was younger than those in the non-ESBL group (6.26 months old). Conversely, Kim YH et al found that the mean age of infants in the ESBL group (4.2 months old) was older than in the non-ESBL group (3.1 months old) [ 21 , 22 ]. Furthermore, Awean GZA et al observed that the majority of infected infants were under 1 year old in both the ESBL group (45.6%) and the non-ESBL group (39.2%) [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the ESBL group was associated with a high recurrence rate (34%), as observed in our study. 14 These discrepant clinical responses and readmission rates may relate to differences in patient population.…”
Section: Discussionmentioning
confidence: 99%